The novel immunobiotic Clostridium butyricum S-45-5 displays broad-spectrum antiviral activity in vitro and in vivo by inducing immune modulation - Chathuranga, Kiramage; Shin, Yeseul; Uddin, Md Bashir; Paek, Jayoung; Chathuranga, W. A. Gayan; Seong, Yebin; Bai, Lu; Kim, Hongik; Shin, Jeong Hwan; Chang, Young-Hyo; Lee, Jong-Soo (Frontiers in Immunology, 2023)
Clostridium butyricum is known as a probiotic butyric acid bacterium that can improve the intestinal environment. In this study, we isolated a new strain of C. butyricum from infant feces and evaluated its physiological characteristics and antiviral efficacy by modulating the innate immune responses in vitro and in vivo. The isolated C. butyricum S-45-5 showed typical characteristics of C. butyricum including bile acid resistance, antibacterial ability, and growth promotion of various lactic acid bacteria.As an antiviral effect, C. butyricum S-45-5 markedly reduced the replication of influenza A virus (PR8), Newcastle Disease Virus (NDV), and Herpes Simplex Virus (HSV) in RAW264.7 cells in vitro. This suppression can be explained by induction of antiviral state in cells by induction of antiviral, IFNrelated genes and secretion of IFNs and pro-inflammatory cytokines. In vivo, oral administration of C. butyricum S-45-5 exhibited prophylactic effects on BALB/c mice against fatal doses of highly pathogenic mouse-adapted influenza A subtypes (H1N1, H3N2, and H9N2). Before challenge with influenza virus, C. butyricum S-45-5 treated BALB/c mice showed increased levels of IFN-β, IFN-γ, IL-6, and IL-12 in serum, the small intestine and bronchoalveolar lavage fluid (BALF), which correlated with observed prophylactic effects. Interestingly, after challenge with influenza virus, C. butyricum S-45-5 treated BALB/c mice showed reduced levels of pro-inflammatory cytokines and relatively higher levels of anti-inflammatory cytokines at days 7 post-infection. Taken together, these findings suggest that C. butyricum S-45-5 plays an antiviral role in vitro and in vivo by inducing an antiviral state and affects immune modulation to alleviate local and systemic inflammatory responses caused by influenza virus infection. Our study provides the beneficial effects of the new C. butyricum S-45-5 with antiviral effects as a probiotic.